Co(II), Cu(II) and Zn(II) Complexes of N, O-Type Schiff Base Ligand Derived from 4,4?-Methylenedianiline Synthesis, Characterization, Antibacterial and Antifungal Studies - Sahal, Hakan; Canpolat, Erdal; Kaya, Mehmet; Gur, Seher (Chem Soc Pakistan, 2017)
Three new complexes were prepared reacting Co(II), Cu(II) and Zn(II) salts with 2-[(E)-{[4-(4-aminobenzyl) phenyl]imino}methyl]-6-ethoxyphenol (LH) and characterized by analytical and spectrocemical methods. The metal: ligand stoichiometric ratio is 1:1 in the complexes of Co(II) and Zn(II), whereas in the Cu(II) complex, the metal: ligand stoichiometric ratio is 2:1. It was determined that bidentate behavior of the ligand is accomplished via the phenolic oxygen and the azomethine nitrogen atoms. The presence of water is revealed by thermograms and supported by the presence of relevant bonds in their IR spectra. These new complexes showed a reasonable amount antifungal activity.
Keywords: Schiff base; Antimicrobial activity; Antifungal activity; Transition metal complexes